Mobile Health Technology for the Personalized Therapy of Hemophilia - Dirzu, Noemi; Hotea, Ionut; Jitaru, Ciprian; Brinza, Melen; Urian, Laura; Peters, Mareike-Catrina; Gal, Krisztina; Popescu, Louis; Blag, Cristina; Marian, Mirela; Pal, Eva; Stanescu, Marilena; et al. (Frontiers in Medicine, 2021)
The management of patients with haemophilia has evolved significantly since the first treatment attempts were made in the late 1930s. Since then, each new step in the treatment of patients with haemophilia has brought important advancements, as well as its unique set of challenges. Today, a patient-centered, individualized comprehensive approach is the new paradigm, moving away from the traditional ‘one size-fits-all’ approach, to provide the best possible care for each patient with a bleeding disorder. As part of this complex task, mobile health applications might have the capacity to play an important role in reaching that goal. However, the use of new electronic technologies as part of a comprehensive treatment approach for patients with haemophilia simultaneously presents a new set of challenges that needs consideration. In the first section, currently available treatment of haemophilia patients will be revised, while in the second part the role of IT software in the treatment monitoring of haemophilia patients will be discussed.